Численные оценки токов и сил в линейных инструментах магнитно-импульсного притяжения металлов. Часть 1: металлы с низкой удельной электропроводностью - Батыгин, Юрий Викторович; Чаплыгин, Евгений Александрович; Шиндерук, Светлана Александровна; Стрельникова, Виктория Анатольевна (Национальный технический университет "Харьковский политехнический институт", 2019)
Целью статьи является проведение численных оценок основных характеристик электродинамических процессов в линейных инструментах магнитно-импульсного притяжения проводников с однонаправленными токами в условиях интенсивного проникновения действующих электромагнитных полей в металлы с низкой удельной электропроводностью. Методика. Для проведения вычислений использовались положения теории электромагнитного поля, вытекающие из уравнений Максвелла, и стандартные математические программы из пакета «Wolfram Mathematica». Результаты. С помощью аналитических выражений рассчитаны амплитудно-временные зависимости токов и электродинамических усилий в линейных магнитно-импульсных инструментах, действенность которых основана на возбуждении сил взаимного притяжения проводников с однонаправленными токами. Впервые установлено, что увеличение сил притяжения, в первую очередь, возможно за счет интенсификации процессов проникновения полей, что обеспечивается переходом к достаточно низким рабочим частотам возбуждающих токов. Практическая значимость. Использование полученных результатов позволит создавать новые более эффективные линейные инструменты магнитно-импульсного притяжения заданных участков листовых металлов, работающие в условиях интенсивного проникновения возбуждаемых электромагнитных полей.

Purpose.The electrodynamics processes study in the linear tools of magnetic-pulsed attraction, the final result of which should be the physics-mathematical dependencies for the characteristics of the flowing processes, under the conditions of intensive penetra-tion in metal of acting electromagnetic fields, as well as numerical estimates of these processes main characteristics. Methodology.To carry out research, we used the fundamental statements of the electromagnetic field theory and the mathematical simulation with help of the standard codes from the Wolfram Mathematica pack-age. Results.The functional dependencies for the spacetemporal distributions of the currents and forces excited in the linear tools of magnetic-pulsed attraction under intensive penetration of the acting electromagnetic fields through the tool's conducting con-struction elements are used for the numerical estimates. From the calculation results it follows that from a physical point of view, the cause of the increase in attractive forces while decreasing the operating frequencies can be considered the intensification of penetration processes of the excited fields, which leads to increas-ing the magnetic pressure from the outside. Thus, the transition to low operating frequencies of the exciting currents can significantly increase the efficiency of the magnetic-pulsed attraction of the sheet metals with the linear tools. Originality.It was firstly determined that from the physical point of view, the reason for the increase in attractive forces witha decrease in operating frequencies can be considered the intensification of penetration processes of the excited fields, which leads toincreasing the forces of magnetic pressure on the conductors from side of their external surfaces. Practical value.A usage of the obtained results will allow creating new, more efficient linear tools of magnetic-pulsed attraction of the low-electrical conduction sheet metals operating under conditions of intensive penetration of the electromagnetic fields being excited.
Numerical estimates of currents and forces in linear tools of the magnetic-pulse attraction of metals. Part 1: Low electrical conductance metals
Keywords: линейный инструмент устранения вмятин в листовых проводниках; интенсивное проникновение поля в металлы с низкой удельной электропроводностью; linear tool for eliminating dents in sheet conductors; intensive penetration of the field into metals with low electrical conductance